2018
DOI: 10.1108/mip-03-2017-0047
|View full text |Cite
|
Sign up to set email alerts
|

Examining need for uniqueness in emerging markets

Abstract: Purpose The purpose of this paper is to conduct a five-country study of consumers’ need for uniqueness (CNFU) and examine its research and practical implications. Most studies examining CNFU have used single country or US-based samples. To promote cross-cultural research, the authors test the cross-cultural reliability and validity of the CNFU scale using data from the USA, a developed economy, Brazil, India, Thailand, and Mexico, all emerging economies. Design/methodology/approach The original CNFU scale wa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
11
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(12 citation statements)
references
References 59 publications
1
11
0
Order By: Relevance
“…The need for uniqueness reflects the differences in consumers concerning counter-conformity motivation, which is the drive to pursue differentness relative to others. Consumers constantly use their distinctive possessions to develop, enhance, and showcase their unique self-image (Sharma et al , 2018). Thus, the search for uniqueness is a continual process which drives consumers to exhibit behaviors contrary to the prevailing norms to maintain their distinctiveness over time.…”
Section: Theoretical Framework and Model Developmentmentioning
confidence: 99%
See 1 more Smart Citation
“…The need for uniqueness reflects the differences in consumers concerning counter-conformity motivation, which is the drive to pursue differentness relative to others. Consumers constantly use their distinctive possessions to develop, enhance, and showcase their unique self-image (Sharma et al , 2018). Thus, the search for uniqueness is a continual process which drives consumers to exhibit behaviors contrary to the prevailing norms to maintain their distinctiveness over time.…”
Section: Theoretical Framework and Model Developmentmentioning
confidence: 99%
“…The present study considered three consumer dispositions – cosmopolitanism, need for uniqueness, and materialism – in examining the attitude toward global brands from developed and emerging markets. These three positive dispositions or personality traits are studied as they are indicative of a perspective beyond provincial consumption boundaries and incorporate diversity, rationality, uniqueness, and material gain (Sharma et al , 2018). While prior studies have individually shown that these three dispositions lead to a positive orientation toward global brands, there is a lack of empirical evidence in the literature regarding the potential differences in their effects on global brands from developed and emerging markets (Bartsch et al , 2016).…”
Section: Introductionmentioning
confidence: 99%
“…Consumer need for uniqueness is a psychological trait that propels individuals to establish distinct personal and social images (Tian and McKenzie, 2001). It represents counter-conformity motivation that highlights individual differences concerning others (Sharma et al , 2018). The need for uniqueness is displayed by acquiring differentiated items and brands (Roy and Rabbanee, 2015).…”
Section: Theoretical Backgroundmentioning
confidence: 99%
“…Second, managerial decisions in emerging markets seem to be different from traditional markets. Business models, for example, need to adapt (Pels and Sheth, 2017) and for companies based in an emerging market, this is no different (Sharma et al, 2018), mainly due to the existence of political, business, social and internal contingencies for companies (Paul, 2020). The last reason refers to particular event factors that vary from country to country, which may base managerial decisions in this very particular context (Lim et al, 2017).…”
Section: Introductionmentioning
confidence: 99%
“…Another striking feature of decision-making is that managers usually rely on subjective judgments and rules of thumb decisions (Leeflang et al, 2015). Context in emerging markets seems to resemble and even intensify this characteristic, as they present particular forms of unstructured and unorganized retail competition (Kumar et al, 2015;Sharma et al, 2018). Distribution strategies vary across brands, product forms and retail competition (Sharma et al, 2019).…”
Section: Introductionmentioning
confidence: 99%